Effect of cytokines on the in vitro fungicidal activity of monocytes from paracoccidioidomycosis patients - Calvi, Sueli Aparecida [UNESP]; Peracoli, MTS; Mendes, Rinaldo Poncio [UNESP]; Marcondes-Machado, J.; Fecchio, Denise [UNESP]; Marques, Silvio Alencar [UNESP]; Soares, AMVC (Elsevier B.V., 2003)
Peripheral blood monocytes obtained from paracoccidioidomycosis patients and healthy individuals were preactivated with recombinant gamma interferon (IFN-gamma) in different concentrations (250, 500 and 1000 U/ml) and evaluated for fungicidal activity against Paracoccidiodes brasiliensis strain 18 (Pb 18, high-virulence strain) and strain 265 (Pb 265, low-virulence strain) by plating of cocultures and counting of colony-forming units, after 10 d. Monocytes from healthy individuals failed to present fungicidal activity against P. brasiliensis even after IFN-gamma activation at the three concentrations. However, patient, monocytes activated with IFN-gamma (1 000 U/ml) showed a significant fungicidal activity when compared to that obtained with non-activated or activated cells with other IFN-gamma concentrations (250 and 500 U/ml). Moreover,,patient monocytes presented higher fungicidal activity than the control, even before the activation process. These results may be explained by the activation state of patients' cells as a function of the in vivo contact with the fungus, which was confirmed by their higher capacity to release H2O2 in vitro. Unlike the results obtained with Ph 18, patient and control cells presented a significant fungicidal activity against Pb 265, after priming with IFN-gamma. These results are explained by the higher levels of TNF-alpha in supernatants of cultures challenged with Pb 265. Moreover, higher levels of the cytokine were obtained in patient cell supernatants. Taken together, our results suggest that for effective killing of P. brasiliensis by monocytes, an initial activation signal induced by IFN-gamma is necessary to stimulate the cells to produce TNF-alpha. This cytokine may be involved, through an autocrine pathway, in the final phase activation process. The effectiveness of this process seems to depend on the virulence of the fungal strain and the activation state of the challenged cells. (C) 2003 Editions scientifiques et medicales Elsevier SAS. All fights reserved.
Keywords: monocyte; fungicidal activity; cytokines; paracoccidioidomycosis; Paracoccidioides brasiliensis